Process Improvement for Error Records in a Financial Institution with the Analysis of Simulation on Using Value Stream Mapping - İbrahim Yel; Orhan Engin (Journal of Advanced Research in Natural and Applied Sciences)
Value stream mapping is an important tool used in process improvement in many industries. In this study, the error records opened by the end-users to the developers who developed the screens over the software development process in the Information Technologies (IT) group of a financial institution operating in the field of participation banking were examined. This paper has been addressed in order to reduce the operational risks that may arise during the resolution of the error records encountered during the use of the software. In financial institutions, customer satisfaction is closely related to the continuity of operational processes in financial transactions. First, the authors draw the current value stream map base on the approval and solution process adventure of these error records were handled in the processing logic, analyzed and a value stream map was drawn for the current situation. Then, based on the information obtained from the current situation, approval flow of the error records is simulated with the Arena simulation program. The obtained simulation results were discussed with the stakeholders of the error resolution process. Bottleneck activities have been identified through the current situation simulation outputs. A new value stream map has been prepared, based on the seven wasteful milestones defined in the lean production philosophy. Finally, the working style of the new situation developed was adapted to the process, remodeled on the Arena software and the new model was analyzed. The simulation results showed that the error/help call records decreased by 79.8% in the in-process return volume.